2014
DOI: 10.2147/ndt.s59600
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic and cognitive changes in children with cerebral palsy: an Egyptian study

Abstract: BackgroundCerebral palsy (CP) is the most frequent cause of motor handicap among children.Aim of the studyWe aim to study the relation of epilepsy in children with CP to various risk factors that affect the development of seizures.Patients and methodsIn a cross-sectional, descriptive, population-based, case-control study, 98 children with CP (48 children with CP with epilepsy, and 50 children with CP without epilepsy) were compared with 180 children without CP or seizures. The children lived in two regions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(45 reference statements)
0
2
1
Order By: Relevance
“…Epilepsy is common in cerebral palsy, present in 30%–40% of cases [ 4 , 16 ], and seizures are reported on 35.5% of CP children in the hemiplegia subgroup [ 15 ]. In the 93 children analyzed in the present study, the incidence of epilepsy was calculated to be 49%, on average higher than that reported in the literature [ 16 , 17 , 18 ]. The difference in the frequency of CP-epilepsy association may depend on the selection of the cases.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Epilepsy is common in cerebral palsy, present in 30%–40% of cases [ 4 , 16 ], and seizures are reported on 35.5% of CP children in the hemiplegia subgroup [ 15 ]. In the 93 children analyzed in the present study, the incidence of epilepsy was calculated to be 49%, on average higher than that reported in the literature [ 16 , 17 , 18 ]. The difference in the frequency of CP-epilepsy association may depend on the selection of the cases.…”
Section: Discussioncontrasting
confidence: 68%
“…In terms of children with CP, grey matter lesions are more common. As suggested by El-Tallawy et al [ 18 ], neonatal seizures can be a strong predictor of epilepsy in cerebral palsy. Sadowska et al [ 19 ] investigated 181 children with CP and selected 102 children affected by epilepsy (56.35%); among this group, 44 (43%) had drug-resistant epilepsy and only 15 (14.71%) were responsive to treatment.…”
Section: Discussionmentioning
confidence: 96%
“…More CP patients with epilepsy had a history of neonatal seizures than non-epilepsy patients. Previous studies by Karatoprak et al [6], Kulak and Sobaniec [16], and El-Tallawy et al [7] also showed that neonatal seizures were a risk factor for epilepsy. An association between epilepsy and history of febrile seizures was observed in our study.…”
Section: Risk Factors For Epilepsy In Cerebral Palsymentioning
confidence: 87%
“…had epilepsy [5][6][7][8][9][10]. The prevalence of epilepsy in the general population is 3 to 8 per 1,000 persons, and the prevalence in patients with CP is higher than that [8,9,11,12].…”
mentioning
confidence: 99%
“…This difference may depend on case selection, where the frequency of epilepsy is greater in the group of CP subjects with spastic quadriplegic type, and with more severe motor dysfunction, as reported in the literature, which may be a reflection of the severity of damage to the brain. (20)(21)(22) The prevalence of vitamin D deficiency in children with cerebral palsy varies throughout the world. In this study, of 85 children with cerebral palsy, 54.1% had deficiency, and 29.4% had vitamin D insufficiency.…”
Section: Discussionmentioning
confidence: 99%